A Study of Enriched CO2 on the Remediation of Heavy Metal Contaminated Soil Using Jatropha Curcas - Cedric , Lemuel Lee (IRC, 2016)
Heavy metal contamination can be found vastly in the soils due to industrial exposure. Without any treatment of the soil, heavy metal can bring harm to the environment and eventually risk the health of humans because of its toxicity. Remediation ensures the safety towards human health and the environment. Phytoremediation is one of the remediation methods that is favoured, as it is .a cost effective method. Nevertheless, phytoremediation does have its drawbacks, which is mainly time. This remediation process using plants may take up to decades in order to fully remediate a contaminated area.